Mammomonogamus nematodes in felid carnivores: a minireview and the first molecular characterization. Issue 14 (21st May 2018) - Červená, Barbora; Hrazdilová, Kristýna; Vallo, Peter; Ketzis, Jennifer; Bolfa, Pompei; Tudor, Edgar; Lux-Hoppe, Estevam G.; Blanvillain, Caroline; Modrý, David
Abstract: Five of the 13 known species of Mammomonogamus have been described in members of the family Felidae, including domestic cats, making felids the most frequent hosts of Mammomonogamus. The occurrence of Mammomonogamus in felids is geographically scattered and information on the life cycle and other aspects of infections is lacking. The paucity of data opens the questions on possible conspecificity of some of the described species of Mammomonogamus and on the existence of possible reservoirs for infections in domestic cats in geographically isolated endemic foci of infection. To test such hypotheses, we compared sequences of mitochondrial and nuclear markers obtained from Mammomonogamus adults or eggs collected from domestic cats in three geographically distant localities. Based on morphology, geographic origin and site of infection, the worms examined can be referred to as Mammomonogamus ierei and Mammomonogamus auris . Phylogenetic analyses of both mitochondrial and ribosomal DNA markers showed monophyly of the genus Mammomonogamus and suggested the existence of at least two species in cats. Review of the literature, the existence of several species and the discontinuous geographic distribution of Mammomonogamus infections in domestic cats suggest an historical spillover of infection from wild reservoirs, presumably wild felids.